CERTAINTY REGARDING LEGAL CHOICES BETWEEN RELIGIOUS COURTS AND DISTRICT COURTS REGARDING APPLICATIONS FOR DETERMINING HEIRS - Jaya, Febri; Fitri, Winda; Besouw, Leny Pelita (Universitas Bengkulu, 2023)
In accordance with the research title listed above, Indonesia has three legal systems that regulate inheritance, namely; Islamic inheritance law which is based on and uses the holy book Al-Quran as its source, western civil inheritance law which originates from Burgerlijk Wetboek (hereinafter referred to as the Civil Code), and finally customary inheritance law based on the customs of the community itself, this cannot be separated from from the role of each court that handles it. Therefore, the author needs to conduct research on the certainty of legal choices between religious courts and district courts regarding applications for determining heirs. The aim of the research is to analyze the role of the district court and religious court in the application for determining heirs, after that this study will also analyze how legal certainty is provided regarding the legal choice between the district court and the religious court. The results obtained from this research are that the implementation of Law no. 50 of 2009 regarding every application for determining Islamic heirs must be handled and under the authority of a religious court, in fact this does not mean that the district court is of the opinion that it no longer has the right and authority to adjudicate applications for inheritance, this is because the authority possessed by the district court still has power. law in an effort to adjudicate applications for determining inheritance for Muslims. However, what needs to be underlined is that the difference between religious courts is that when it comes to resolving inheritance cases, religious courts are guided by the complications of Islamic law, while district courts are based on the Civil Code, namely western law. Keywords:District Court, Religious Court, Inheritance, Petition, Determination